WANPRESTASI PADA JUAL BELI ONLINE DENGAN SISTEM DROPSHIP DI KOTA PEKANBARU (STUDI KASUS TOKO SUPLIER PRODUK RUMAH TANGGA EKSLUSIF E-COMMERCE DUSDUSAN) - Ghairi, Syafwan; Deliana, Evi; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Electronic transactions set forth in electronic contracts bind the parties, in online buying and selling themselves regarding a person or party who is in default which is contained in the Articles of the Civil Code can be asked for compensation as the act has violated the law contained in Article 1365 of the Civil Code, and if it turns out that the goods do not match what was photographed as a form of the offer, it is part of a default, which is where Subekti argues that the default is negligence or negligence. Problems that are often found in transaction practice include product errors sent by the seller to the buyer, the color does not match with the original order, size error to the address details sent by the buyer to the seller. With these errors and omissions resulting in a loss to the buyer, the buyer will lose financially directly due to fraud, lost the opportunity to make a sale and purchase due to service interruptions, unexpected losses such as interference from outside parties, human factor errors or electronic system errors, problems trust in security guarantees, from the buyer's side he receives a product that is not in accordance with what was ordered to the seller, while the seller often has to cover the lack of postage due to an error in the address data sent by the buyer. This research is to find out to find out buying and selling with the dropshiping system in the city of Pekanbaru and to find out the responsibility of the dropshipper by consumers if there is a loss in transactions with the dropshiping system in the city of Pekanbaru. The type of research in this thesis is sociological law research. The conclusions obtained from the results of the study are 1. The implementation of e-commerce transactions by dusdusan.com is in accordance with applicable state law, this is in accordance with the validity of the applicable agreement theory according to the Criminal Code, where e-commerce transactions are a new theory. the agreement can clearly discuss the legal position in the transaction, the position includes the Criminal Code and the ITE Law. The responsibility carried out by the dropshipper follows from the applicable policy in the village, then this is also in accordance with the theory of responsibility which according to Hans Kelsen in his theory of legal responsibility states that: "a person is legally responsible for a certain act or that he bears legal responsibility. Keyword : Default-Dropship-Dudsdusan